Optimizing Ecological Economy Practices for Sustainable Agri-Food Networks: Deli Serdang and Simalungun Comparative Study - Annisa Ilmi Faried (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines and compares ecological economy optimization strategies within sustainable agri-food systems across two contrasting administrative regions of North Sumatra, Indonesia. The research aims to evaluate implementation effectiveness, identify performance differentials, and develop strategic frameworks to enhance sustainable agricultural development considering socio-economic and environmental diversity. A mixed-methods comparative design was applied, combining quantitative surveys of 450 agricultural stakeholders per district with qualitative interviews involving key informants such as policymakers, producers, and supply chain actors. Quantitative data included environmental impact, economic performance, and supply chain efficiency indicators, analyzed using multivariate regression and structural equation modeling. Findings reveal that Deli Serdang demonstrates higher technological adoption (78.4%) and operational efficiency (91.2%) than Simalungun (61.7% and 76.8%), driven by infrastructure advantages and urban proximity. Conversely, Simalungun shows greater engagement in organic farming (68.9%) and stronger community-based sustainability practices. Both regions face constraints in sustainable financing access and technical capacity for green supply chain implementation. This research introduces the first dual-regional framework for ecological economy assessment in Indonesian agri-food systems, offering a scalable model for tropical developing contexts. The results support Indonesia’s Green Economy Index initiatives and inform policy design for sustainable food system transformation.